Project WRITE (Writing Inclusive Text on Ethnicity) in Mind - Sampang, Jethro Jake; Pecson, Ryan; dela Rosa, John Albert; Reyes, Jeniel; Marticio, Benjun; Quinto, Ronald (PT. Riset Press International, 2025)
Language can be a powerful conveyor of bias in both blatant and subtle forms. Language bias can impact race and ethnicity as it echoes stereotypical perceptions about other people and their actions. To avoid language biases in instructional materials developed and/or used by teachers, an extension project is proposed by the College of Education (COEd) of Bataan Peninsula State University (BPSU) in cooperation with the City Schools Division Office (SDO) of Balanga City to train teacher-writers on text-based biases based on ethnicity, empowering them on developing instructional resources (i.e., self-learning materials) to promote cultural sensitivity and alleviating ethnicity-grounded biases on learning materials used in Grades 1 to 3 among public schools. The extension project commenced after the Memorandum of Agreement (MOA) between the university and the SDO. The extension project employed the facilitated group extension method in training teacher-writers. Select 30 teacher-writers from Grades 1 to 3, teaching Araling Panlipunan (Social Studies) and Edukasyon sa Pagpapahalaga (Values Education), are purposively selected to serve as the project beneficiaries. The extension team conducted a series of training sessions, material development (learning activity sheets), technical assistance, monitoring, and evaluation of the project to ensure its success. At the outset, the extension project has achieved the following: determined the needs, strengths, and challenges of teacher-writers in identifying text-based biases in ethnicity in the learning materials used as bases for needs improvement; provided seminar-workshops in tracing text-based biases and writing culture sensitive self-learning materials free from language biases based on ethnicity; developed and utilized teachers’ guide in addressing text-based biases and writing culture-sensitive self-learning materials; and established linkage/partnership to improve culturally-sensitive instructional practices. Additionally, three research publications have emerged as by-products of the extension project. To ensure sustainability, the project has been adopted by other schools division (SDO-Bataan).